2008
DOI: 10.12968/bjon.2008.17.20.45121
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of workplace violence directed at nurses

Abstract: The consequences of workplace violence (WPV) are far-reaching, and impact on the nurse, the perpetrator and the organization. However, the authors were unable to identify any research in the literature on nurses' perceptions of the consequences of WPV in non-teaching hospital settings. This study therefore aimed to examine nurses' perspectives of the consequences of WPV, to identify ways to reduce the impact of these incidents. A descriptive, exploratory approach was adopted to collect qualitative survey and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…13 Although a recent study found that verbal abuse was less damaging than physical abuse in terms of the effect it has on the quality of patient care, 12 the available evidence unequivocally demonstrates the negative impacts of verbal abuse and bullying in the workplace on both the quality of the delivery of health services and the health and wellbeing of victims. [12][13][14]16,19,[21][22][23][24][25] Instances of inmate initiated verbal abuse may be fuelled, in part, by environmental and structural factors, such as gaol crowding and a lack of relevant vocational programs for inmates. 30 Implementation of strategies that address such factors may be effective in reducing incidents of verbal abuse perpetrated against correctional health professionals, and may also reduce the already relatively low risk of physical abuse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Although a recent study found that verbal abuse was less damaging than physical abuse in terms of the effect it has on the quality of patient care, 12 the available evidence unequivocally demonstrates the negative impacts of verbal abuse and bullying in the workplace on both the quality of the delivery of health services and the health and wellbeing of victims. [12][13][14]16,19,[21][22][23][24][25] Instances of inmate initiated verbal abuse may be fuelled, in part, by environmental and structural factors, such as gaol crowding and a lack of relevant vocational programs for inmates. 30 Implementation of strategies that address such factors may be effective in reducing incidents of verbal abuse perpetrated against correctional health professionals, and may also reduce the already relatively low risk of physical abuse.…”
Section: Discussionmentioning
confidence: 99%
“…In individual health professionals, exposure can lead to physical injury, anger, fear, sadness, helplessness, stress, anxiety, a loss of self-confidence and, in extreme cases, post-traumatic stress disorder and/ or suicidal ideation, 14,16,19,[21][22][23][24][25] all of which can place strain on relationships with work colleagues, family members and friends. 21,24,25 At the health facility level, workplace abuse has been linked to employee absenteeism, low workplace morale, staff turnover, reduced empathy for patients, reduced productivity at work, and increased risk of errors in the delivery of care, 12,13,16,19,21,[23][24][25] all of which can undermine the quality of the delivery of health services. 12,19,21,24,25 In addition, the direct and indirect financial costs of workplace abuse, incurred by individuals, health organisations and the broader community, are substantial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to the risk of violence among men in the Work and Health survey for the whole working population, whereas women in general experienced violence twice as often as hospital employees [25]. We assume that there was more violence in hospitals than this study showed, because employees did not report every violent act and especially verbal aggression, when they considered it part of everyday work [27]. Thus underreporting of violence in hospitals is possible.…”
Section: Discussionmentioning
confidence: 82%
“…Psychiatric units are one of the most frequent sites of workplace violence, especially physical violence (WPV) [12], and primary care staff such as nurses are the people most frequently assaulted by patients [13]. Even among nurses who see WPV as ''part of their job,'' occurrences can still leave them feeling incompetent, cause them to suffer physical and emotional harm, make them avoid patients and disrupt patient care [14]. Although Alsaker et al [15] found that women who experienced domestic violence had very low HRQoL scores, and Johansen et al [16] indicated that the presence of post-traumatic stress disorder symptoms predicted lower quality of life (QOL) in victims of non-domestic violence, the relationship of QOL to WPV in psychiatric settings is still unclear.…”
Section: Introductionmentioning
confidence: 99%